Final victory the life and death of Naval Pirojsha Godrej - Karanjia, B. K. (New Delhi Viking, 2000)
Biography of Naval Pirojsha Godrej, b. 1916-1990, Indian industrialist.
Keywords: Godrej, Naval Pirojsha -- 1916-1990.; Industrialists -- India -- Biography; Parsees -- Biography